Quaternized chitosan-coated nanoemulsions: A novel platform for improving the stability, anti-inflammatory, anti-cancer and transdermal properties of Plai extract. (15th February 2020) - Luesakul, Urarika; Puthong, Songchan; Sansanaphongpricha, Kanokwan; Muangsin, Nongnuj
Graphical abstract: The stability and bioactivity, including the anti-inflammatory activity and skin permeability, of the secondary emulsion coated with QCS (NE2-QCS) compared with the primary emulsion (NE1) Highlights: A new positively charged nanoemulsion system using quaternized chitosan (QCS) as a protective layer was demonstrated. NE2-QCS could improve the stability of lipophilic active components during 28-day storage compared with NE2-CS and NE1. NE2-QCS significantly exhibited a stronger anti-inflammatory ability (82.1 % NO inhibition) than NE1 (69.5 % NO inhibition). NE2-QCS increased the permeability by approximately 1.5-fold compared with NE1. Abstract: A new positively charged nanoemulsion using quaternized chitosan (QCS) as a protective layer was developed to improve the stability and bioactivity of lipophilic active components. The anti-inflammatory Plai extract was chosen as both an active ingredient and an oil phase of the system. Compared with chitosan-coated nanoemulsion (NE2-CS) and uncoated nanoemulsion (NE1), the QCS coating could improve the stability of the Plai extract during 28 days. The particle size of NE1 increased from 141 nm to 202 nm after coating with QCS, whereas zeta potential changed from -22.03 mV for NE1 to 20.23 mV for NE2-QCS, confirming the presence of QCS. A clear improvement in anti-inflammatory, anti-cancer, and transdermal properties of Plai extract was verified for NE2-QCS, which could be due to the NEs' fineness and the permanent positive charge of the protective layer. Therefore, we suggested that QCS-coated NEs can be used as an effective transdermal delivery system for lipophilic active components.